Biochemical mechanisms preventing wilting under grafting: a case study on pumpkin rootstock grafting to wax gourd - Fu, Houlong; Fu, Junyu; Zhou, Bin; Wu, Haolong; Liao, Daolong; Liu, Zifan (Frontiers in Plant Science, 2024)
Wax gourd wilt is a devastating fungal disease caused by the specialized form of Fusarium oxysporum Schl. f. sp. benincasae (FOB), which severely restricts the development of the wax gourd industry. Resistant rootstock pumpkin grafting is often used in production to prevent and control wax gourd wilt. The 'Haizhan 1' pumpkin has the characteristic of high resistance to wilt, but the mechanism through which grafted pumpkin rootstock plants acquire resistance to wax gourd wilt is still poorly understood.In this study, grafted wax gourd (GW) and self-grafted wax gourd(SW) were cultured at 3 concentrations [2.8×106 Colony Forming Units (CFU)•-1,8.0×1 5 CFU•g-1 and 4.0×105 CFU•g-1, expressed by H, M, and L].Three culture times (6dpi,10dpi and 13dpi) were used to observe the incidence of wilt disease in the wax gourd and the number of F. oxysporum spores in different parts of the soil and plants. Moreover, the physiological indices of the roots of plants at 5 dpi,9 dpi and 12 dpi in soil supplemented with M (8.0×105 CFU•g-1) were determined. No wilt symptoms in GW.Wilt symptoms in SW was exacerbated by the amount of FOB in the inoculated soil and culture time. At any culture time, the amount of FOB in the soil of GW under 3 treatments were greater than that in the roots. However, for the SW treatments, after 10 dpi and 13 dpi, the amount of FOB in the soil was lower than that in the roots. The total phenol(TP) and lignin(LIG) contents and the polyphenol oxidase(PPO) and chitinase(CHI) activities significantly increased in the GWM roots. The activities of phenylalanine ammonia lyase(PAL) and peroxidase(POD) decreased first but then increased in the GWM roots. When the TP content decreased significantly, the LIG content, and PAL and CHI activities increased first but then decreased, while the PPO and POD activities did not change significantly in the SWM roots. The results indicated that the roots of the 'Haizhan 1' pumpkin stock plants initiate a self-defence response after being infected with FOB; additionally, the activities of PPO, POD, PAL and CHI increase, and additional LIG and TP accumulate, which can effectively prevent FOB infection.